2014
DOI: 10.1021/jm401937a
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Novel Antidepressants Targeting α4β2-Nicotinic Acetylcholine Receptors

Abstract: Nicotinic acetylcholine receptors (nAChRs) have been investigated for developing drugs that can potentially treat various central nervous system disorders. Considerable evidence supports the hypothesis that modulation of the cholinergic system through activation and/or desensitization/inactivation of nAChR holds promise for the development of new antidepressants. The introductory portion of this Miniperspective discusses the basic pharmacology that underpins the involvement of α4β2-nAChRs in depression, along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 140 publications
0
41
0
Order By: Relevance
“…Collectively, cumulative testimonies gained both from preclinical and clinical examinations confirmed that the cholinergic system acts a deciding character in cognitive function (Yu et al, 2014;Sarter and Kim, 2015). Further, concrete loss of the nAChRs is perceived in degenerative neurological disorders such as Alzheimer's disease with specific relation of the a7 nAChR subtype (Taly et al, 2009;Chiang and Koo, 2014).…”
Section: Introductionmentioning
confidence: 88%
“…Collectively, cumulative testimonies gained both from preclinical and clinical examinations confirmed that the cholinergic system acts a deciding character in cognitive function (Yu et al, 2014;Sarter and Kim, 2015). Further, concrete loss of the nAChRs is perceived in degenerative neurological disorders such as Alzheimer's disease with specific relation of the a7 nAChR subtype (Taly et al, 2009;Chiang and Koo, 2014).…”
Section: Introductionmentioning
confidence: 88%
“…Indeed, the cognitive-enhancing effects of nicotinic receptor targeting compounds are currently being investigated in Alzheimer's disease (Valles et al 2014), autism (Ghaleiha et al 2013), attention deficit (hyperactivity) disorder (Childress and Sallee 2014; Fleisher and McGough 2014), depression (Yu et al 2014), schizophrenia (Freedman 2014), and healthy individuals (Demeter and Sarter 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, did not find evidence for these neuropsychiatric side effects (Cinciripini et al, 2013;Garza et al, 2011;Thomas et al, 2013). Nevertheless, a recent study suggests that varenicline may have a protective effect on depressed mood (Cinciripini et al, 2013); furthermore, α4β2 nAChR as potential antidepressant targets have been implicated (Yu et al, 2014). Therefore, a significant genetic association with suicidal phenotype among smokers is highly relevant and can provide an important basis for further pharmacogenetic studies of the CHRNB2 gene because vulnerability to suicidal behavior can be a key to choosing safer cessation therapy.…”
Section: Total Population Males Femalesmentioning
confidence: 99%